2014
DOI: 10.1111/brv.12157
|View full text |Cite
|
Sign up to set email alerts
|

The role of skeletal‐muscle‐based thermogenic mechanisms in vertebrate endothermy

Abstract: Thermogenesis is one of the most important homeostatic mechanisms that evolved during vertebrate evolution. Despite its importance for the survival of the organism, the mechanistic details behind various thermogenic processes remain incompletely understood. Although heat production from muscle has long been recognized as a thermogenic mechanism, whether muscle can produce heat independently of contraction remains controversial. Studies in birds and mammals suggest that skeletal muscle can be an important site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
174
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(195 citation statements)
references
References 231 publications
(394 reference statements)
2
174
0
1
Order By: Relevance
“…We propose that SLNmediated uncoupling of SERCA leads to an increase in cytosolic Ca 2ϩ and activation of CaMKII by phosphorylation at Thr 286 . Phosphorylation of RyR1 increases Ca 2ϩ leaking from the SR, increasing SERCA activity, setting up a leak reuptake cycle analogous to the functioning of the heater organ in endothermic fishes (21). Based on our data and results published previously, it seems possible that activation of CaMKII is a coldinduced, Ca 2ϩ -sensitive molecular response conserved in diverse life forms (40).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We propose that SLNmediated uncoupling of SERCA leads to an increase in cytosolic Ca 2ϩ and activation of CaMKII by phosphorylation at Thr 286 . Phosphorylation of RyR1 increases Ca 2ϩ leaking from the SR, increasing SERCA activity, setting up a leak reuptake cycle analogous to the functioning of the heater organ in endothermic fishes (21). Based on our data and results published previously, it seems possible that activation of CaMKII is a coldinduced, Ca 2ϩ -sensitive molecular response conserved in diverse life forms (40).…”
Section: Discussionsupporting
confidence: 71%
“…[13][14][15][16][17][18][19] and reviewed in Ref. 20,21). Recently, we reported that modulation of SER Ca 2ϩ cycling by sarcolipin (SLN) in skeletal muscle plays an important role in NST (13,14,(22)(23)(24).…”
mentioning
confidence: 99%
“…Collectively, these findings along with our data suggest that SLN is an important marker of muscle-based thermogenesis. Interestingly, SLN is expressed abundantly in adult skeletal muscles of large mammals including dog, rabbit and pig, which contain only negligible amounts of or non-functional BAT (Rowland et al, 2014), indicating that muscle-based NST may play a greater role in such animals. Therefore, determining the physiological relevance of high levels of SLN in these species will be instrumental in better understanding muscle-based NST.…”
Section: Resultsmentioning
confidence: 99%
“…Further, with muscle being dispersed throughout the body, it can provide heat locally, rather than needing to be circulated by the blood from a localized BAT. Hence, during the evolution of endothermy in individual species, a combination of BAT and muscle-based thermogenesis has been selected that provides the best survival outcome (13).…”
Section: Discussionmentioning
confidence: 99%